Laparoscopic resection of a neuroendocrine tumor that almost fully replaced tailgut cysts: a case report - Keita Kodera; Seiichiro Eto; Nei Fukasawa; Wataru Kai; Tomo Matsumoto; Tsuyoshi Hirabayashi; Hidejiro Kawahara; Nobuo Omura (Surgical Case Reports)
Abstract Background Neuroendocrine tumors (NETs) originate from neuroendocrine cells, which are found throughout the body. NETs occur principally in the gastrointestinal tract (approximately 65%) and bronchopulmonary tract (approximately 25%) but rarely occur in the presacral space. Aside from primary and metastatic lesions, there have been reports of NETs occurring in the presacral space arising from tailgut cysts, teratomas, and imperforate anus. We herein report a rare case of laparoscopic resection of a NET in the presacral space, which almost fully replaced tailgut cysts. Case presentation A 68-year-old woman was referred to our hospital for surgery of a right inguinal hernia, but preoperative computed tomography revealed an asymptomatic 43-mm mass in the presacral space. Magnetic resonance imaging showed a multilocular solid mass with clear boundaries and a slightly high signal intensity on T1- and T2-weighted images. Positron emission tomography showed 18F-fluorodeoxyglucose uptake. Thus, we suspected a malignant tumor and performed laparoscopic resection to obtain a definitive diagnosis. Macroscopically, the tumor was 43 mm in size with clear boundaries, and the cut surface was a gray-white solid component. Histopathological findings revealed that the tumor was composed of relatively uniform cells with fine chromatin, with round to oval nuclei arranged in solid, trabecular, or rosette-like growth patterns. Small cysts lined with stratified squamous epithelium and columnar epithelium were observed along with solid components of the tumor, which is a feature of tailgut cysts. Therefore, the final diagnosis was NET Grade 1 arising from tailgut cysts. No recurrence was observed within 1 year after surgery. Conclusions We performed en bloc laparoscopic resection of a NET arising from tailgut cysts in the presacral space without injury. In cases of a solid lesion in the presacral space, not only the primary disease but also the pathological condition with tissue transformation and replacement should be considered, as in this case.